Coral-like polymer microspheres and preparation method and application thereof
Thiolated PAMAM microspheres loaded with metal copper quantum dots were prepared by reverse phase emulsion polymerization to form a coral-like structure, solving the problem of poor temperature and salt resistance during deep migration of the reservoir, and achieving efficient deep sealing and oil dispersion effects.
Patent Information
- Application Number
- CN202411766724.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing polymer microspheres have poor temperature and salt resistance during deep migration of reservoirs and poor sealing performance, making it difficult to meet the deep-draining requirements in the later stage of high-water reservoir development.
Reverse emulsion polymerization method was used to prepare thiolated PAMAMs with metal copper quantum dots as matrix, and combined with azo initiators to form coral-like polymer microspheres. By adjusting the morphology and size, the microsphere improves shear resistance, salt resistance and temperature resistance, and enhances the sealing and oil dispersion capabilities.
It realizes effective sealing and regulation of deep strata, improves recovery rate, maintains stability in high temperature and high salt environments, and extends the service life of microspheres.
Smart Images

Figure CN119219837B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petrochemical industry, and particularly relates to coral-shaped polymer microspheres and a preparation method and application thereof. Background Art
[0002] The commonly used displacement technology has achieved remarkable results in the actual application of oil fields, but the traditional displacement agent also has some shortcomings. For example, although the granular displacement agent has high strength and can well plug the high permeability layer, it mainly improves the seepage near the injection well and increases the swept volume near the injection well. Its deep profile adjustment effect is not great. The granular displacement agent often has a large particle size and mainly plugs the oil layer near the injection well. However, the residual oil saturation near the injection well is small, and the degree of recovery improvement is very low. The injected water will eventually bypass and enter the high permeability layer again. Although the underground cross-linked organic displacement system has the characteristics of mobility and can reach the deep part of the reservoir for displacement, its plugging strength cannot meet the requirements of the high permeability formation. After a short period of plugging, it will be broken through by the injected water and has a short effective period. Therefore, based on the actual needs of the late stage of high water-cut oil reservoir development, the development of a deep displacement agent with long-term effectiveness and certain strength has become the core issue currently faced.
[0003] Deep profile control technology refers to the use of various organic and inorganic profile control and water plugging agents such as gel foam and polymer microspheres. These profile control and water plugging agents can penetrate deep into the reservoir, block high permeability reservoirs, force liquids to flow to low permeability reservoirs, and increase the volume of injected water in medium and low permeability reservoirs, thereby improving the recovery rate.
[0004] At present, polymer microspheres mainly have good water absorption and expansion performance, but large particle size, poor temperature and salt resistance, and will be damaged during migration to deep reservoirs, resulting in shallow penetration of polymer microspheres into the formation or poor plugging performance in deep reservoirs. Therefore, the development of microspheres with high temperature and salt resistance and strong formation penetration ability is the key to improving deep reservoir plugging.
[0005] Quantum dots are a new type of semiconductor nanomaterial, a type of semiconductor nanoparticle composed of II-VI or III-V elements with a radius smaller than or close to the exciton Bohr radius. Due to the influence of quantum size effect and dielectric confinement effect, quantum dots have unique properties, which makes quantum dots have great application potential in the fields of oil extraction and catalysis. The prior art generally directly uses quantum dots as tracers or oil displacement agents, and the application range is relatively narrow. CN115306362A directly uses quantum dots as oil displacement agents, and uses the extremely strong penetration and oil washing effects of quantum dots to penetrate into the rock surface to remove the oil film and improve the oil washing efficiency; however, its cost is relatively high, and it does not have the effect of blocking and regulating displacement. CN115181217A prepares core-shell microspheres with fluorescent tracing function, by introducing fluorescent quantum dots in the process of preparing the core microsphere solution, and then mixing and adsorbing with the shell monomer water to prepare the core-shell microsphere solution. The fluorescent quantum dots are located inside the core-shell fluorescent microspheres and will not detach, thereby improving the subsequent detection accuracy. The quantum dot microspheres are prepared into microspheres of ordinary morphology by direct in-situ polymerization process, and only the tracer function of quantum dots is used for detection, and the plugging and flooding effect is limited. The fluorescent microspheres prepared by CN117736722A, CN115247060A, etc. have smooth surfaces and cannot be used as flooding agents. Summary of the invention
[0006] The purpose of the present invention is to provide a coral-shaped polymer microsphere and its preparation method and application in view of the defects of the prior art. By adjusting the morphology and size of the polymer microsphere, the polymer microsphere has the characteristics of easy injection, high plugging strength and strong adjustment ability, and has good shear resistance, salt resistance and temperature resistance, good expansion performance, and can achieve the purpose of deep plugging and profile adjustment of the formation.
[0007] The technical solution for achieving the purpose of the present invention is as follows:
[0008] A method for preparing coral-like polymer microspheres comprises the following steps:
[0009] (1) adding thiolated PAMAM to a mixed solution containing metallic copper quantum dots, performing ultrasonic dispersion, and drying to obtain thiolated PAMAM loaded with metallic copper quantum dots; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is (0.001-0.02):1;
[0010] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a cross-linking agent are added to water respectively, an alkali solution is added to adjust the pH, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0011] (3) Add surfactant and azo initiator to the organic solvent, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase;
[0012] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiol-containing PAMAM loaded with metal copper quantum dots is added while stirring, and then the reaction is carried out at a temperature of 55-75°C for 1-3 hours to obtain coral-like polymer microspheres.
[0013] In the previous work (CN118580443A), the inventor used silica of different particle sizes as reinforcing fillers and prepared polyacrylamide microspheres by dispersion polymerization, which improved the heat resistance and salt resistance of the microspheres to a certain extent. However, the microspheres have a smooth surface, large particle size, and limited oil displacement effect. Subsequently, the inventors prepared solid polymer microspheres of various morphologies. Although their plugging ability was improved to a certain extent, the particle size was large or the "tentacles" were short, and the improvement in oil displacement ability was limited. In order to further improve the plugging and oil displacement ability of polymer microspheres, the present invention introduces a dendritic PAMAM (polyamide-amine) polymer with a thiol end group as a matrix, prepares thiol-loaded PAMAM with metal copper quantum dots, and adds an oil-soluble azo initiator at the same time, and prepares coral-like polymer microspheres by inverse emulsion polymerization.
[0014] PAMAM is a typical dendrimer. Compared with other traditional dendrimers, PAMAM has a large number of surface functional groups, intramolecular cavities and nanometer-scale dimensions, which provide a basis for loading quantum dots. Since the hydrocarbon chains in PAMAM dendrimers are lipophilic groups, but the carboxyl and amino groups they contain are hydrophilic groups, they not only have solubilizing and stabilizing effects, but can also combine with quantum dots through electrostatic adsorption; on the other hand, the presence of a large number of cavities on the surface and inside of PAMAM also helps with loading quantum dots.
[0015] However, directly using PAMAM cavities and electrostatic adsorption as the binding force for loading metal copper quantum dots will lead to uneven loading of metal copper quantum dots, unable to form a spatially ordered structure, and the binding force is weak, which will cause the quantum dots to fall off during the stirring process, affecting the stability of the product structure. In order to improve the stability and uniformity of PAMAM-loaded metal copper quantum dots, the present invention selects a dendritic PAMAM (polyamide-amine) polymer with a thiol end group as a matrix to load metal copper quantum dots. Compared with functional groups such as carboxyl and amino groups, thiol groups have a very strong coordination effect with copper metal. PAMAM ligands containing thiol groups can firmly bind to quantum dots and can be used as stabilizers to prepare stable quantum dot dispersions. Since PAMAM has a high degree of geometric symmetry, the active groups on its surface are evenly distributed, and the surface becomes more and more crowded with the growth of generations. By introducing dense thiol functional groups on the surface of PAMAM, strong coordination bonds can be formed with quantum dots, and the quantum dots can be evenly fixed on the outer surface of PAMAM.
[0016] Metallic copper quantum dots are more active than copper oxide quantum dots; and because of their large surface area to volume ratio, the copper atoms exposed on the surface can provide a large number of active sites, thereby enhancing catalytic activity. The unpaired electrons of metallic copper quantum dots can be conjugated with the double bonds of acrylamide monomers, and free radicals can be generated to initiate polymerization reactions without the need for chemical initiators. Under heating conditions, the initiation rate is accelerated while the monomer conversion rate is also accelerated. Compared with the previous technology of loading copper oxide quantum dots on large-particle mesoporous microspheres and preparing microspheres with azo substances as initiators, the present invention uses copper quantum dots loaded on thiol-PAMAM as a matrix and azo initiators to initiate polymerization to prepare microspheres. The surface of the microspheres presents a coral-like cross-linear structure, and its water absorption and swelling ability and plugging ability are enhanced, which can greatly improve the plugging and oil displacement rate of the microspheres.
[0017] Moreover, the present invention adopts the inverse emulsion polymerization method to prepare polymer microspheres, and the oil-soluble initiator and the water-soluble monomer solution are uniformly dispersed in the oil phase continuous phase through the emulsification effect of the surfactant, and the polymerization is initiated in the oil-in-water reaction system by the thiol-PAMAM loaded with metal copper quantum dots and the oil-soluble initiator. The polymerization process is milder than the dispersion polymerization method, and the conditions are easy to control. Further, the present invention first drops the aqueous phase into the oil phase to form an emulsion, and then adds the thiol-PAMAM loaded with metal copper quantum dots. PAMAM itself has strong hydrophilicity and is easy to disperse in aqueous solution, while metal copper quantum dots are lipophilic substances; it can be seen that the thiol-PAMAM loaded with metal copper quantum dots has both hydrophilic and lipophilic ends, and has some properties similar to surfactants. When the thiol-PAMAM loaded with metal copper quantum dots is added to the emulsion, it is easier to disperse at the interface between the two phases, and the azo initiator is easier to disperse in the organic phase. Since the metal copper quantum dots have high catalytic activity, when heating begins, they will preferentially initiate monomers to polymerize with the thiol-modified PAMAM loaded with metal copper quantum dots as the core. Due to the unevenness of the catalysis of the spherical metal copper quantum dots, the growth rate of the shell polymer is inconsistent. In this process, the azo initiator enriched in the oil phase takes the irregularities on the surface of the shell as the core, further initiating the polymerization reaction of the monomer. In this process, the polymer core initiated by the metal copper quantum dots and the polymer shell initiated by the azo initiator continue to grow, and finally form an interactive coral-like structure on the surface of the microsphere. The surface of the polymer microsphere prepared by the present invention presents an interlaced coral-like morphology. Compared with the lychee-like and rambutan morphologies, the interactive structure can not only effectively disperse the expansion stress and avoid the expansion and rupture phenomenon after water absorption, but also enhance the mutual force between the microspheres, and the plugging effect is better. At the same time, as the microspheres absorb water and expand, the long "tentacles" on their appearance also expand accordingly, and the expanded "tentacles" play the role of cross-linking the microspheres, which can achieve a better plugging effect.
[0018] Furthermore, the specific preparation process of the thiolated PAMAM in step (1) is as follows: add thioglycolic acid or methyl thioglycolate to the aqueous solution of the amino PAMAM, stir for reaction, and dry under reduced pressure to obtain the thiolated PAMAM. The PAMAM with ethylenediamine as the core of the present invention is synthesized by diffusion method. First, the central core ethylenediamine and methyl acrylate are subjected to complete Michael addition reaction to obtain a half-generation PAMAM with an ester end group; the second step is to carry out amidation reaction between the ester end group half-generation PAMAM and excess ethylenediamine to obtain a first-generation PAMAM with an amino end group. Repeating the above two steps can obtain PAMAMs of different integer generations that are continuously increasing. The outer layer of the integer-generation PAMAM dendrimer has a large number of amino groups, and the hydrocarbon chain inside it is a lipophilic group, so PAMAM has the dual role of a carrier and a surfactant. The amino active groups on the surface of PAMAM are combined with quantum dots using thiol compounds as a connecting bridge, which, on the one hand, reduces the surface energy of the quantum dots and improves their dispersibility; on the other hand, it can prevent the metal copper quantum dots from being oxidized or agglomerated, and improve the stability of the quantum dots in the solvent.
[0019] Furthermore, the amino PAMAM is a PAMAM of 4-10 integer generations; the molar ratio of the amino group on the amino PAMAM to thioglycolic acid or methyl thioglycolate is 1:(1.1-1.5); the stirring reaction temperature is 45-55°C, and the reaction time is 7-10h. Furthermore, the mass ratio of the metal copper quantum dots to the thioglycolated PAMAM is (0.01-0.015):1; by adjusting the amount of quantum dots, the particle size of the polymer microspheres and the coral-like morphology size can be adjusted.
[0020] Furthermore, the alkali solution in step (2) is a sodium hydroxide solution or a potassium hydroxide solution.
[0021] Furthermore, in step (2), the pH is 6-7.
[0022] Furthermore, in step (2), the cross-linking agent is N,N-methylenebisacrylamide.
[0023] Furthermore, in step (3), the surfactant is one or both of Span-80 and Tween-80; the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptylnitrile; and the organic solvent is white oil. Due to the different dispersion properties of the thiol-PAMAM loaded with metal copper quantum dots and the azo initiator in the solvent, the positions and rates of the polymerization initiated by the two in the inverse emulsion polymerization process are different. Due to the uneven catalysis of the spherical metal copper quantum dots, the growth rate of the shell polymer is inconsistent. In this process, the azo initiator enriched in the oil phase uses the irregularities on the surface of the shell as the core to further initiate the polymerization reaction of the monomer, thereby promoting the formation of the surface uneven morphology.
[0024] Furthermore, the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metallic copper quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.05-0.2): 1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metallic copper quantum dots is (70-80): (85-100): 1.
[0025] On the other hand, the present invention also provides a coral-like polymer microsphere and its application as a profile control and oil displacement agent. Acrylamide-based polymer is a synthetic polymer used to enhance oil displacement. It has excellent rheological properties and is one of the most commonly used polymers in oil displacement applications. Due to the presence of a strong hydrophilic group, the polyacrylamide microsphere has good water absorption and swelling properties. It can absorb water and swell in the deep reservoir, plug the gaps, increase the volume of injected fluid, and thus improve the recovery rate. In order to enhance the stability of the polymer microspheres in the harsh environment of high temperature and high salt in the reservoir, the main monomer acrylamide (AM) and the functional monomer acrylic acid (AA) are copolymerized, and an appropriate amount of cross-linking agent is added to prepare acrylamide-based quantum dot copolymer microspheres with a cross-linked structure. Compared with the previous microspheres with zero-dimensional or one-dimensional linear protrusions on the surface, the staggered coral-like structure can not only play the role of cross-linking and interlocking to improve the plugging efficiency, but also the coral-like structure has a high water absorption and swelling rate, which can better improve the recovery rate.
[0026] Compared with the existing disclosed technology, the positive effects of the present invention are:
[0027] (1) A simple inverse emulsion polymerization process was used. By adjusting the addition method of azo initiators and thiol-PAMAM loaded with copper quantum dots, the polymer core initiated by copper quantum dots and the polymer shell initiated by azo initiators continued to grow, eventually forming an interactive coral-like structure on the surface of the microspheres.
[0028] (2) The staggered coral-like structure can not only play the role of cross-linking and interlocking to improve the plugging efficiency, but also the coral-like structure has a high water absorption and expansion rate, which can effectively disperse the expansion stress inside the microspheres, promote the stability of the microspheres under high temperature and high salt conditions, and better improve the recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron micrograph of coral-like polymer microspheres prepared in Example 8;
[0030] Figure 2 Another scanning electron micrograph of the coral-like polymer microspheres prepared in Example 8;
[0031] Figure 3 This is a scanning electron micrograph of the polymer microspheres prepared in Comparative Example 1. DETAILED DESCRIPTION
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The present invention will be further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and can implement it, but the embodiments are not intended to limit the present invention.
[0033] Example 1
[0034] A method for preparing coral-like polymer microspheres comprises the following steps:
[0035] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.01:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring for reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.1; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0036] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 6 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0037] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 12:4:0.5:1:4:0.05:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 70:85:1;
[0038] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiolated PAMAM loaded with metal copper quantum dots is added while stirring, and then the mixture is reacted at 55°C for 3 hours to obtain coral-like polymer microspheres.
[0039] Example 2
[0040] A method for preparing coral-like polymer microspheres comprises the following steps:
[0041] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.015:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.5; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0042] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0043] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 16:8:2.5:3:8:0.2:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 80:100:1;
[0044] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiolated PAMAM loaded with metal copper quantum dots is added while stirring, and then the mixture is reacted at 75°C for 1 hour to obtain coral-like polymer microspheres.
[0045] Example 3
[0046] A method for preparing coral-like polymer microspheres comprises the following steps:
[0047] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.01:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.5; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0048] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0049] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 16:4:2.5:1:8:0.05:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 80:100:1;
[0050] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiolated PAMAM loaded with metal copper quantum dots is added while stirring, and then the mixture is reacted at 60°C for 2 hours to obtain coral-like polymer microspheres.
[0051] Example 4
[0052] A method for preparing coral-like polymer microspheres comprises the following steps:
[0053] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.012:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.2; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0054] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 6 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0055] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 13:5:1:1.5:5:0.1:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 75:95:1;
[0056] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiolated PAMAM loaded with metal copper quantum dots is added while stirring, and then the reaction is carried out at 58°C for 2.2 hours to obtain coral-like polymer microspheres.
[0057] Example 5
[0058] A method for preparing coral-like polymer microspheres comprises the following steps:
[0059] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.014:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.4; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0060] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0061] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 15:7:2:2.5:7:0.15:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 78:95:1;
[0062] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiolated PAMAM loaded with metal copper quantum dots is added while stirring, and then the reaction is carried out at 70°C for 1.5 hours to obtain coral-like polymer microspheres.
[0063] Example 6
[0064] A method for preparing coral-like polymer microspheres comprises the following steps:
[0065] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.003:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0066] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0067] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 14:6:1:2:6:0.1:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 75:95:1;
[0068] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiol-containing PAMAM loaded with metal copper quantum dots is added while stirring, and then the mixture is reacted at 65°C for 2 hours to obtain coral-like polymer microspheres.
[0069] Example 7
[0070] A method for preparing coral-like polymer microspheres comprises the following steps:
[0071] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.02:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0072] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0073] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 14:6:1:2:6:0.1:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 75:95:1;
[0074] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiol-containing PAMAM loaded with metal copper quantum dots is added while stirring, and then the mixture is reacted at 65°C for 2 hours to obtain coral-like polymer microspheres.
[0075] Example 8
[0076] A method for preparing coral-like polymer microspheres comprises the following steps:
[0077] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to the thiolated PAMAM is 0.013:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours;
[0078] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0079] (3) Add surfactant and azo initiator azobisisobutyronitrile to organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is 14:6:1:2:6:0.1:1; the mass ratio of water, organic solvent and thiolated PAMAM loaded with metal copper quantum dots is 75:95:1;
[0080] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiol-containing PAMAM loaded with metal copper quantum dots is added while stirring, and then the mixture is reacted at 65°C for 2 hours to obtain coral-like polymer microspheres.
[0081] Comparative Example 1
[0082] The preparation process is basically the same as that of Example 8, except that the metal copper quantum dots with an average particle size of 3 nm are replaced by copper oxide quantum dots with an average particle size of 5 nm.
[0083] Comparative Example 2
[0084] The preparation process is basically the same as that of Example 8, except that in step (1), the mass ratio of metallic copper quantum dots to thiolated PAMAM is 0.06:1.
[0085] Performance Test:
[0086] The polymer microspheres prepared in Examples 1-8 and Comparative Examples 1-2 were dispersed in simulated formation water with a mineralization of 30,000 mg / L, and expanded at 80° C. for different time periods. The expansion multiples were measured. The results are shown in Table 1.
[0087] Low permeability cores were selected for evaluation of oil recovery effect: first, the cores were saturated with simulated formation water to determine their pore volume; then, the cores were saturated with simulated crude oil; the cores were displaced with simulated formation water until the outlet end stopped producing oil, and the recovery factor A was determined; polymer microsphere dispersion was injected into the cores and placed at 65°C for 5 days; the cores were displaced with simulated formation water again until the outlet end stopped producing oil, and the recovery factor B was determined; the recovery factor increase was C (%) = (BA) / AX 100%, and the results are shown in Table 1.
[0088]
[0089] Depend on Figure 1-2 It can be seen that the coral-like polymer microspheres prepared by the present invention have a relatively uniform particle size distribution, and a linear coral-like structure is distributed on the surface. This indicates that due to the different dispersion properties of the thiol-PAMAM loaded with metal copper quantum dots and the azo initiator in the solvent, there are differences in the location and rate of polymerization initiated by the two during the reverse emulsion polymerization process. Due to the uneven catalysis of the spherical metal copper quantum dots, the growth rate of the shell polymer is inconsistent. In this process, the azo initiator enriched in the oil phase uses the irregularities on the surface of the shell as the core to further initiate the polymerization reaction of the monomer and promote the formation of uneven surface morphology. The polymer core initiated by the metal copper quantum dots and the polymer shell initiated by the azo initiator continue to grow, and finally form an interactive coral-like structure on the surface of the microsphere.
[0090] It can also be seen from the data in Table 1 that the coral-like polymer microspheres prepared by the present invention can not only effectively disperse the expansion stress and avoid the expansion and rupture phenomenon after absorbing water, but also enhance the interaction force between the microspheres, and the plugging effect is better. At the same time, as the microspheres absorb water and expand, the long "tentacles" on their surface also expand accordingly, and the expanded "tentacles" play the role of cross-linking the microspheres, which can achieve a better plugging and oil displacement effect.
[0091] Depend on Figure 3It can be seen that comparative example 1 uses copper oxide quantum dots to replace metal copper quantum dots, and polymers with regular morphology cannot be prepared. This is because copper oxide quantum dots themselves do not have the function of initiators; and in the reverse emulsion polymerization, the thiol-containing PAMAM loaded with metal copper quantum dots has both a hydrophilic end and a lipophilic end, and it has some properties similar to surfactants. When the thiol-containing PAMAM loaded with metal copper quantum dots is added to the emulsion, it is more easily dispersed at the interface between the two phases, while the azo initiator is more easily dispersed in the organic phase. It can be seen that, unlike the dispersion polymerization method, the thiol-containing PAMAM loaded with metal copper quantum dots and the azo initiator are dispersed in different solvent systems, which makes it difficult for copper oxide quantum dots to adsorb azo initiators and promote the formation of irregular morphology. Comparative Example 2 shows that when the amount of quantum dots is too much, not only will they agglomerate and lose the catalytic effect of the quantum dots, but also the lipophilic quantum dots themselves will affect the hydrophilic-lipophilic balance value of the thiol-PAMAM loaded with metallic copper quantum dots, which is not conducive to the stability of the emulsion system and causes the oil displacement ability of the polymer microspheres to deteriorate.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing coral-like polymer microspheres, characterized in that: The following steps are involved: (1) adding thiolated PAMAM to a mixed solution containing metallic copper quantum dots, performing ultrasonic dispersion, and drying to obtain thiolated PAMAM loaded with metallic copper quantum dots; the mass ratio of the metallic copper quantum dots to the thiolated PAMAM is (0.001-0.02):1; (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a cross-linking agent are added to water respectively, an alkali solution is added to adjust the pH, and nitrogen is passed to deoxygenate to obtain an aqueous phase; (3) Adding a surfactant and an azo initiator to an organic solvent, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptylnitrile; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, azo initiator and thiolated PAMAM loaded with metal copper quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.05-0.2): 1; (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, nitrogen is passed through to deoxygenate, and the thiol-containing PAMAM loaded with metal copper quantum dots is added while stirring, and then the reaction is carried out at a temperature of 55-75°C for 1-3 hours to obtain coral-like polymer microspheres.
2. The method for preparing coral-like polymer microspheres according to claim 1, characterized in that: The specific preparation process of the thiolated PAMAM in step (1) is as follows: adding thioglycolic acid or methyl thioglycolate to the aqueous solution of amino PAMAM, stirring for reaction, and drying under reduced pressure to obtain the thiolated PAMAM.
3. The method for preparing coral-like polymer microspheres according to claim 2, characterized in that: The aminated PAMAM is a PAMAM of 4-10 integer generations; the molar ratio of the amino group on the aminated PAMAM to thioglycolic acid or methyl thioglycolate is 1:(1.1-1.5); the stirring reaction temperature is 45-55°C, and the reaction time is 7-10h.
4. The method for preparing coral-like polymer microspheres according to claim 1, characterized in that: The alkali solution in step (2) is a sodium hydroxide solution or a potassium hydroxide solution.
5. The method for preparing coral-like polymer microspheres according to claim 1, characterized in that: The pH in step (2) is 6-7.
6. The method for preparing coral-like polymer microspheres according to claim 1, characterized in that: In step (2), the cross-linking agent is N,N-methylenebisacrylamide.
7. The method for preparing coral-like polymer microspheres according to claim 1, characterized in that: In step (3), the surfactant is one or both of Span-80 and Tween-80; and the organic solvent is white oil.
8. The method for preparing coral-like polymer microspheres according to claim 1, characterized in that: The mass ratio of water, organic solvent and thiolated PAMAM loaded with metallic copper quantum dots is (70-80):(85-100):
1.
9. A coral-like polymer microsphere, characterized in that: The coral-like polymer microspheres are prepared by the preparation method of any one of claims 1 to 8.
10. Use of the coral-like polymer microspheres according to claim 9 as a profile control and oil displacement agent.
Citation Information
Patent Citations
Quantum dot light-emitting film, preparation and application of quantum dot light-emitting film in white-light Mini-LED device
CN115247060A
Application of quantum dots in unconventional oil reservoir exploitation, oil-displacing agent and method for increasing yield by using oil-displacing agent
CN115306362A
High-brightness and high-stability water-soluble quantum dot fluorescent microsphere and preparation method thereof
CN117736722A
Temperature-resistant and salt-resistant polymer microsphere and preparation method thereof
CN118580443A
High-strength fluorescent hydrogel and preparation method thereof
CN105504364A